2020
DOI: 10.3390/v12090930
|View full text |Cite
|
Sign up to set email alerts
|

Peste des petits ruminants Virus Transmission Scaling and Husbandry Practices That Contribute to Increased Transmission Risk: An Investigation among Sheep, Goats, and Cattle in Northern Tanzania

Abstract: Peste des petits ruminants virus (PPRV) causes an infectious disease of high morbidity and mortality among sheep and goats which impacts millions of livestock keepers globally. PPRV transmission risk varies by production system, but a deeper understanding of how transmission scales in these systems and which husbandry practices impact risk is needed. To investigate transmission scaling and husbandry practice-associated risk, this study combined 395 household questionnaires with over 7115 cross-sectional serosu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 42 publications
0
19
0
Order By: Relevance
“…During the dry season, the pastoral communities in Uganda tend to move animals over long distances within and sometimes outside the national borders in search for pastures and water for their livestock. This husbandry practice increases chances of infected and naïve flocks interacting hence potentially facilitating PPRV transmission and increasing the number of outbreaks (Herzog et al., 2020). Additionally, the likelihood of animal nose‐to‐nose contact and therefore PPRV transmission especially at communal watering points increases during the dry season (VanderWaal et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…During the dry season, the pastoral communities in Uganda tend to move animals over long distances within and sometimes outside the national borders in search for pastures and water for their livestock. This husbandry practice increases chances of infected and naïve flocks interacting hence potentially facilitating PPRV transmission and increasing the number of outbreaks (Herzog et al., 2020). Additionally, the likelihood of animal nose‐to‐nose contact and therefore PPRV transmission especially at communal watering points increases during the dry season (VanderWaal et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors for PPRV infection were investigated by eight of the eligible studies, using questionnaires and sero-prevalence data. The risk factors identified as major contributors to PPR occurrence in Tanzania included communal grazing and housing (14,42,55,56); the practice of selling sick animals at cheap prices and bought by livestock keepers for slaughtering in other villages (14); the mixing of infected with healthy animals in markets; and poor access to veterinary services (14).…”
Section: Risk Factorsmentioning
confidence: 99%
“…Recently, GIS spatial analysis has been widely used in the risk analysis of animal diseases, such as African swine fever, bluetongue, bird flu, and foot and mouth disease, to reveal the relationship and spatial pattern of disease transmission (Andraud et al., 2021; Malesios et al., 2020; Ozdenerol, 2015; Sham et al., 2014; Zhang et al., 2015). However, although many efforts have been made to explore and analyse PPR outbreaks, few studies have reported PPR outbreaks using spatial analysis (Balamurugan et al., 2021; Herzog et al., 2020; Rahman et al., 2021; Ruget et al., 2019). In China, only two papers have analysed PPR outbreaks using spatial analysis (Gao et al., 2019; Ma et al., 2019b).…”
Section: Introductionmentioning
confidence: 99%